Brain's Night Symphony (BraiNSy): A Methodology for EEG Sonification - Fernandes, Carlos M.; Migotina, Daria; Rosa, Agostinho C. (IEEE transactions on affective computing, 2021)
This paper describes a method for converting sleep Electroencephalogram (EEG) signals into music. For that purpose, a new segmentation procedure is used for extracting relevant information from the sleep EEG that is then translated into sequences of notes, chords, arpeggios and pauses, with a varying tempo that is defined by sleep stages. The final outcome is a direct time-domain conversion of the brain activity during sleep into sound. Since typical sleep EEGs vary with age and sleep disorders, different groups of subjects were used in the experiments: babies, sane adults and patients with air-flow limitation.